Забезпечення надійності організаційних процесів інвестиційно-будівельних проектів - Ваколюк, А. С. (Ways to Improve Construction Efficiency, 2014)
The article presents the basic principles of reliability and risk assessment of organizational processes of investment and construction projects developed by the relevant rating system and a mechanism to ensure the reliability and reduce risks.